1997
DOI: 10.2337/diacare.20.7.1093
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Concentrations of Insulin and Proinsulin-Like Molecules With Coronary Heart Disease Prevalence and Incidence: A study of two ethnic groups

Abstract: We have found similar relationships between concentrations of proinsulin-like molecules and prevalent coronary heart disease, as are observed for insulin in these nondiabetic subjects, although these molecules comprise only approximately 10% of all insulin-like molecules. It appears biologically implausible that these relationships represent cause and effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 17 publications
(28 reference statements)
6
35
0
Order By: Relevance
“…27 Thus, rather than being directly associated with its cause, proinsulin may be a marker of an underlying metabolic disturbance predisposing to atherosclerosis. 7 In vitro, proinsulin increases the plasminogen activator inhibitor-1 (PAI-1) production, 28 and in humans, plasma proinsulin was directly associated with PAI-1 concentrations. 29 PAI-1, as a major inhibitor of fibrinolysis, has the capacity of constituting an important factor in the pathogenesis of atherothrombosis preceding the onset of ischemic heart disease by several years at the population level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Thus, rather than being directly associated with its cause, proinsulin may be a marker of an underlying metabolic disturbance predisposing to atherosclerosis. 7 In vitro, proinsulin increases the plasminogen activator inhibitor-1 (PAI-1) production, 28 and in humans, plasma proinsulin was directly associated with PAI-1 concentrations. 29 PAI-1, as a major inhibitor of fibrinolysis, has the capacity of constituting an important factor in the pathogenesis of atherothrombosis preceding the onset of ischemic heart disease by several years at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…30 A lag phase of 5 years between the elevated plasma proinsulin and the increased risk of CHD (Figure 2) may explain why 2 shorter studies failed to reveal the association. 7,31 The few clinical trials comparing human proinsulin and insulin treatment in diabetic subjects have shown that the overall frequency of cardiovascular events was 7 to 18 times higher when human proinsulin was administrated for 1 to 2 years, compared with that of human insulin. 32 The attained plasma proinsulin concentrations were clearly supraphysiological, but on the other hand, the higher cardiovascular event rate became apparent after a comparatively short time period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In prospective studies, the relationship of proinsulin to cardiovascular disease has been variable. Yudkin et al 13 found a significant relationship in a cross-sectional but not prospective study from the United Kingdom. Conversely, Lindahl found that high proinsulin concentrations in Swedish subjects predicted acute myocardial infarction 14 and stroke.…”
Section: ;105:1311-1316mentioning
confidence: 92%
“…Among both diabetic and nondiabetic subjects, proinsulin has exhibited moderate but significant associations with blood pressure (BP) and concentrations of total cholesterol, triglycerides, LDL and HDL cholesterol (20 -24), and plasminogen activator inhibitor type 1 (25) independent of other factors included in multivariate analysis. However, the role of elevated proinsulin in atherogenesis remains controversial (23,26).…”
mentioning
confidence: 99%